PENGARUH GAYA HIDUP, LINGKUNGAN SOSIAL, DAN PENGALAMAN KEUANGAN TERHADAP MANAJEMEN KEUANGAN MAHASISWA DENGAN KECERDASAN EMOSIONAL SEBAGAI VARIABEL MODERASI - Nofiana, Nadiya Ferlita Nofiana; Dwi Puji Astuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of lifestyle, social environment, and financial experience on the manajemen keuangan of Economic Education students at Universitas Negeri Semarang, with emotional intelligence as a moderating variable. The research employed a quantitative approach with data collected through questionnaires distributed to 202 respondents selected using simple random sampling techniques. The research instruments were tested for validity and reliability and analyzed using classical assumption tests and Moderated Regression Analysis (MRA) with the assistance of SPSS version 27. The results showed that lifestyle had no significant effect on manajemen keuangan, while social environment and financial experience had a positive and significant effect on students’ manajemen keuangan. In addition, emotional intelligence was able to strengthen the influence of lifestyle and financial experience on manajemen keuangan, but it was unable to moderate the influence of social environment on manajemen keuangan. The coefficient of determination (R²) value of 0.977 indicates that 97.7% of the variation in manajemen keuangan can be explained by the variables in this study, while the remaining 2.3% is influenced by other factors outside the study. Improving financial experience, a positive social environment, and emotional intelligence are important factors in enhancing the quality of students’ manajemen keuangan.